2005
DOI: 10.1111/j.1365-2028.2005.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological impact of tobacco farming in miombo woodlands of Urambo District, Tanzania

Abstract: This paper examines the ecological threat of tobacco farming in Urambo District, the leading producer of flue‐cured tobacco in Tanzania with other major producers being Tabora, Iringa and Chunya Districts. Structured interviews were conducted in four villages while 39 Modified‐Whittacker plots were laid in tobacco fallow lands for inventory of woody species to ascertain ecological performance and the impact of tobacco on species diversity, richness and standing stock functions. There was higher than expected s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 5 publications
(6 reference statements)
2
23
1
3
Order By: Relevance
“…With more technical agricultural practices beyond the reach of small-scale tobacco growers, production expansion is only possible through the clearing of additional forest land. Also in Tanzania, Mangora found that virgin land is preferred for tobacco growing because of the fear of soil-borne diseases and the increased yield it provides 23. According to this study, 69% of tobacco farmers in the Urambo District clear new areas of woodlands for tobacco cultivation every season, while only 25% of them grow tobacco on the same plot for two consecutive seasons and only 6% do so for more than two consecutive seasons.…”
Section: Resultsmentioning
confidence: 75%
“…With more technical agricultural practices beyond the reach of small-scale tobacco growers, production expansion is only possible through the clearing of additional forest land. Also in Tanzania, Mangora found that virgin land is preferred for tobacco growing because of the fear of soil-borne diseases and the increased yield it provides 23. According to this study, 69% of tobacco farmers in the Urambo District clear new areas of woodlands for tobacco cultivation every season, while only 25% of them grow tobacco on the same plot for two consecutive seasons and only 6% do so for more than two consecutive seasons.…”
Section: Resultsmentioning
confidence: 75%
“…The mean area of fallow is 2.2 ha, equalling 12% of all landholding. However, only a third of the farmers grow tobacco on the same piece of land for 2 or more consecutive years, which means a shortening of the fallow period to 4 years (while at least 20 years would be required for the restoration of natural fertility) (Mangora, 2005). This implies that a shift has occurred from slash-and-burn agriculture as practiced in the 1970s (Boesen and Mohele, 1979, p.…”
Section: Tanzaniamentioning
confidence: 98%
“…For example, China appears to have achieved an energy transition from wood-to coal-based curing technologies probably about two decades ago (Zhang, 1997), and the preliminary results from this study also prove that the massive deforestation statement applies especially if not exclusively to some growing areas (less so, countries) in the African miombo ecosystem zone (Saloojee, 2004). On the other hand, due to methodological improvements to measure the combined effects of deforestation through land clearance and curing-driven deforestation (Mangora, 2005), the extent of tobacco-related annual deforestation in these growing zones might be considerably higher than estimated in previous studies, which were based on energy needs in curing only (e.g., Geist, 1999). In sum, the usage of terms such as environmental "crisis" (WHO, 2004a, p. 2) or "desertification" (Waluye, 1994, p. 252), used to describe the particular and excessive impact of tobacco curing on native forest cover worldwide with hardly any differentiation made between different growing areas, very likely means an undue inflation of what the term actually implies (O'Connor, 1987).…”
Section: Environmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these data on woodland deforestation are only indicative and may not reflect actual situation on a countrywide scale given that charcoal and firewood is consumed in significant amounts across all other Tanzanian cities. Further, in some parts of Tabora and southern (Iringa and Mbeya) regions deforestation stands at >3% annually in the miombo woodlands (Mangora 2005) because of shifting cultivation and excessive use of woods for curing tobacco (Sauer and Abdallah 2007). For example, the land converted from natural vegetation to cultivated land increased to 11.2% (between 1995 and 2000) from 4.7% (between 1984 and 1995) in some parts of Tabora (Yanda 2010).…”
Section: Habitat Degradation and Loss And Associated Risks Of Speciesmentioning
confidence: 99%